Yunvjian-Medicated Serum Protects INS-1 Cells against Glucolipotoxicity-Induced Apoptosis through Autophagic Flux Modulation. (14th December 2020) - He, Caigu; Zheng, Xuehua; Lin, Xiuhong; Chen, Xinying; Shen, Chenyi
Abstract : Yunvjian (YNJ) is a traditional Chinese medicine formula adopted to prevent and treat diabetes. Our previous results from animal experiments showed that YNJ decreased blood glucose. This study aimed to examine the effect of high glucose and high lipid (HG/HL) conditions on the proliferation and apoptosis of INS-1 cells and the possible protective mechanism of YNJ-medicated serum on INS-1 cells exposed to HG/HL conditions. INS-1 cells were cultured in RPMI 1640 medium after being passaged. Then, INS-1 cells in the logarithmic growth phase were collected and divided into five groups: control, HG/HL, HG/HL+5% YNJ-medicated serum, HG/HL+10% YNJ-medicated serum, and HG/HL+20% YNJ-medicated serum. MTT assay and flow cytometry were used to detect proliferation and apoptosis of INS-1 cells, respectively. Protein profiles of INS-1 cells were analyzed using a tandem mass tag (TMT) label-based quantitative proteomic approach. Western blotting was performed to verify the proteomic results. YNJ-medicated serum significantly promoted INS-1 cell proliferation and inhibited apoptosis. Proteomic results from the INS-1 cells in the control, HG/HL, and HG/HL+10% YNJ-medicated serum groups showed that 7, 468 proteins were identified, of which 6, 423 proteins were quantified. Compared with the HG/HL group, 430 differential proteins were upregulated, and 671 were downregulated in the HG/HL+10% YNJ-medicated serum group. Compared with the control group, 711 differential proteins were upregulated and 455 were downregulated in the HG/HL group, whereas 10 differential proteins were upregulated and 9 were downregulated in the HG/HL+10% YNJ-medicated serum group. Furthermore, several proteins related to autophagy, including ATG3, ATG2B, GABARAP, WIPI2, and p62/SQSTM1, were verified by western blotting, and these results were consistent with the results obtained from the proteomics analysis. These results confirmed that the autophagy pathway is critical to glucolipotoxicity in INS-1 cells. YNJ-medicated serum exhibited a protective effect on INS-1 cells cultured under HG/HL conditions by regulating autophagy genes' expression and restoring the autophagic flux.